IDENTIFIKASI KEMAMPUAN BERPIKIR MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL MATERI BANGUN RUANG SISI DATAR - Shintia Sipa'i; Siti Chotimah (IKIP Siliwangi, 2021)
This study aims to identify students' mathematical thinking skills in questions of flat-sided geometry and evaluate the understanding of class IX students on the previous material. This type of research is a qualitative research with instrument test or posttest without any action beforehand. The questions made by the researcher are questions with the cognitive domains C1-C6, Anderson and Krathwohl's revised Bloom taxonomy with C1 Remember, C2 Understad, C3 apply, C4 analyze, C5 Evaluate, C6 Create. The population used is 25 students with 9 male and 16 female. implementation of research by providing instruments or questions directly. The assessment used is calculated using an assessment formula with an understanding score guideline. The results obtained by students are quite good final scores with specifications C1 getting very good results, C2 getting pretty good results, C3 getting pretty good results, C4 getting pretty good results, C5 getting pretty good results and C6 getting pretty good results. With this fairly good final result, it can be concluded that students in understanding and mastering the flat-sided geometric material learned in class VIII can be remembered well in class IX students by online learning.